The Effect of Capital Structure and Growth on Firm Value with Dividend Policy as a Moderating Variable in FBM KLCI Companies Listed on Bursa Malaysia for the Period 2019–2023 - Mellinda Sri Wardani; Erlina Erlina; Ibnu Austrindanney Sina Azhar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The purpose of this research is to examine and ascertain how capital structure and growth affect company value in FBM KLCI businesses listed on Bursa Malaysia between 2019 and 2023, dividend policy being used as a moderating factor. The study's sample consists of 16 FBM KLCI firms that were listed on Bursa Malaysia between 2019 and 2023. The secondary data utilized was gathered from Bursa Malaysia's website and financial statement documentation studies. Descriptive analysis, panel data regression analysis, MRA, traditional assumption testing, and hypothesis testing are among the data analysis methods used. Eviews Version 13 was used to process the data for this investigation. According to the study's findings, for the 2019–2023 timeframe, capital structure significantly and favorably affects company value in FBM KLCI businesses listed on Bursa Malaysia. In these businesses, growth has no bearing on firm value. In FBM KLCI businesses listed on Bursa Malaysia for the 2019–2023 timeframe, both the correlation between capital structure and company value and the effect of growth on firm value are unaffected by dividend policy.